2014
DOI: 10.1074/jbc.m114.623348
|View full text |Cite
|
Sign up to set email alerts
|

Chrysanthemyl Diphosphate Synthase Operates in Planta as a Bifunctional Enzyme with Chrysanthemol Synthase Activity

Abstract: Background: Chrysanthemyl diphosphate synthase (CDS) is known to catalyze the formation of the irregular terpenoid, chrysanthemyl diphosphate (CPP). Results: CDS also catalyzes the next step from CPP to chrysanthemol. Conclusion: CDS is actually a chrysanthemol synthase (CHS) with bifunctional enzyme activity. Significance: Identification of CHS increases our understanding in terpene biosynthesis and paves the way for engineering biosynthesis of the most widely used natural pesticide, pyrethrins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…5A). As reported previously (Rivera et al, 2001;Yang et al, 2014), the CDS-catalyzed reaction also produces small amounts of lavandulyl diphosphate, causing the transchrysanthemol preparation to contain a small amount of lavandulol (Fig. 5A).…”
Section: Tcadh2 Is a Trans-chrysanthemol Dehydrogenasementioning
confidence: 69%
See 4 more Smart Citations
“…5A). As reported previously (Rivera et al, 2001;Yang et al, 2014), the CDS-catalyzed reaction also produces small amounts of lavandulyl diphosphate, causing the transchrysanthemol preparation to contain a small amount of lavandulol (Fig. 5A).…”
Section: Tcadh2 Is a Trans-chrysanthemol Dehydrogenasementioning
confidence: 69%
“…The mass spectrum-mass spectrum (MS/MS) of this metabolite (Fig. 7E) was identical to that of a compound produced in tobacco (Nicotiana tabacum) expressing TcCDS (Yang et al, 2014) that these workers putatively identified as trans-chrysanthemyl malonylglucoside. In samples expressing TcCDS + TcADH2, a peak with m/z 831.3328 was detected with an MS/MS that closely matched the spectrum of another monoterpene acid glucoside, geranyl-6-O-malonyl-b-D-glucopyranoside (Yang et al, 2011).…”
Section: Transient Coexpression Of Tcadh2 and Tcaldh1 With Cds In N mentioning
confidence: 77%
See 3 more Smart Citations